Minimizing Medication Errors by Triangle Check of Look-Alike Sound-Alike Medications from Crash Cart of Gynecology and Obstetrics in Emergency - Durr- (University of Minnesota Libraries Publishing, 2020)
Background: According to the Joint Commission, crash cart-related patient safety issues are mixed-up medications, medication errors, damaged or expired medicines, improper checking of crash cart and non-competent staff. The availability of crash cart with all the needed emergency items, appropriate clinical protocols and rapid response team are regarded as important tools for the management of clinical emergencies in obstetrics and gynecology. The aim of this study was to design and implement a strategy to prevent the medication errors of look-alike sound-alike medications in emergency situations from the crash cart of gynecology and obstetrics. Method: A nurse was assigned to record all the medications-related events in emergency situations along with receiving the medication order from healthcare professionals and dispensing medications from crash cart of gynecology and obstetrics. Triangle check of look-alike sound-alike medications was regarded necessary. Results: A significant reduction in number of look-alike sound-alike medication errors and near misses was recorded (p<0.05). Discussion: This strategy can be implemented not only to the gynecology and obstetrics but also to other areas of healthcare where look-alike sound-alike medications are stored, dispensed, administered or supplied and will be of great help in emergency situations. Conclusion: A healthcare professional should be assigned at crash cart to record all the medications-related events and triangle check of dispensed look-alike sound-alike medications must be compulsory in emergency conditions.